Properties, benefits and effects of soursop (Annona muricata L.) on blood glucose and cancer - Sosa Crespo, Irving; Pareja Aguiñaga, Jesús Alejandro; Mugarte Moguel, Alfonso Jesús; Chel Guerrero, Luis Antonio; Betancur Ancona, David Abram (Revista Colombiana de Investigaciones Agroindustriales, 2022)
Soursop (Annona muricata L.) is a fruit that has presented various benefits to human health. Different parts of the plant have been used in traditional medicine to reduce inflammation, fever, cough, and asthma. The fruit promotes some antihyperglycemic and weight loss activity in the body; additionally, it has been used as an anticancer remedy. Due to all of the above, this work aimed to review and analyze different results of experimental research conducted with different parts of the soursop, considering its glycemic activity and its antitumor effect, for a possible future application. Several articles, journals, and books from virtual servers which contained the characteristics requested for the topic in question were reviewed to prepare this paper. The results showed the presence of certain components such as tannins, flavonoids, catechins, quercetins, and polyphenols. Among the active principles most present in soursop are the annonaceous acetogenins; these natural phytochemicals produced in the tree’s roots, bark, stems, and leaves, as well as in the fruit’s seeds, have demonstrated diverse beneficial effects. Leaves, fruits, roots, and seeds have been regarded as components with anti-diabetic effects; some research showed that the daily administration of leaf extract in rats decreased blood levels of glucose, triglycerides, and cholesterol; other studies administered an extract of soursop with ginger for thirty days, showing a decrease in liver damage caused by diabetes mellitus. The acetogenins present in soursop have been studied for their antitumor activity since these compounds can selectively inhibit the growth of cancer cells. The fruit's polyphenols have demonstrated antioxidant effects, which could have co-adjuvants effects in cancer treatments. Despite the benefits, caution should be exercised if ingested in large quantities and for prolonged periods due to potentially adverse effects.